Vibration suppression of cables using tuned inerter dampers. (1st September 2016) - Lazar, I.F.; Neild, S.A.; Wagg, D.J.
Highlights: We propose the use of a tuned-inerter-damper (TID) for vibration suppression in cables. The TID performance is analysed in parallel to the performance of viscous dampers. A new procedure for TID systems optimisation is presented. We develop a practical design method for TIDs and dampers, based on contour plots. The improved performance of TIDs is confirmed through numerical simulations. Abstract: This paper considers the use of a tuned inerter damper (TID) system for suppressing unwanted cable vibrations. The TID consists of an inerter, a device that exerts a force proportional to relative acceleration, coupled with a parallel spring and damper. It may be thought of as similar to a tuned-mass-damper, but requiring two terminals. As a two terminal device, the performance of the TID is compared to the classical use of viscous dampers (VD) located close to one of the cable supports. We show that the limitation that exists with VDs, where the modal damping of the cable cannot exceed a maximum level for a given damper location, can be overcome through the use of the TID at the same location. A practical design methodology, based on the minimisation of the displacement amplitude at the mid-span of the cable subjected to support excitation, is proposed. An example where a cable is subjected to the El-Centro earthquake demonstrates that the system's response is improved when a TID is used instead of a VD.